Effect of Repeated Application of Chlorpyrifos on Fungal Population of Pine Forest Soil - Bisht, Jyoti; Harsh, N. S. K.; Palni, L. M. S.; Pande, Veena (Indian Forester, 2016)
Fungi from the natural source can be exploited as an effective tool for biodegradation of toxic xenobiotics. The present investigation has been taken up to study the effect of chlorpyrifos on fungal population and isolate most pesticide tolerant fungal species from pine forest soil in three different culture media (NCM, NSM and NPM). Total thirty two fungal species belonging to eleven genera were isolated from pine forest soil in which Cladosporium cladosporioides, Paecilomyces lilacinus, Penicillium decumbens, P. frequentans, Phoma fimeti, Trichoderma atroviride, T. harzianum and T. viride have ability to tolerate higher concentrations of chlorpyrifos. Maximum CFU count was recorded in NPM in which chlorpyrifos was given as a sole source of phosphorus as compared to other tested culture media. When chlorpyrifos applied in soil at lower doses (1-2 ppm), total CFU count increased between 12.08-13.42X103 CFU g soil-1 . Lower concentrations of chlorpyrifos caused a stimulatory effect on fungal population as they probably utilized it as energy or other nutrient source. However, higher concentrations (5-500 ppm) of chlorpyrifos inhibited the total fungal population.